Hambatan Pemerintah Desa dalam Proses Mediasi Sengketa Warisan Keluarga di Desa Sitampa Simatoras Kecamatan Batang Angkola Kabupaten Tapanuli Selatan - Bandaharo Saifuddin; Marwan Busyro (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the obstacles and role of the Village Government in the mediation process of family inheritance disputes in Sitampa Simatoras Village, Batang Angkola District, South Tapanuli Regency. Land inheritance disputes often cause internal family conflicts that disturb public peace. This study uses a normative and qualitative approach with primary data through interviews and secondary data from literature and laws and regulations. The results of the study show that the Village Head has an important role as a mediator in resolving disputes, but faces various obstacles. The main obstacles include the emotional attitude of the parties to the dispute, the lack of written evidence and witnesses, the low legal knowledge of the village government, and the lack of standard guidelines on mediation mechanisms at the village level. Even so, the Village Head still tries to carry out his role by bringing together the parties and involving traditional leaders to reach a peace agreement. If mediation fails, then the Village Head suggests a settlement through legal channels. This research emphasizes the importance of strengthening the legal capacity of village governments and the need for clearer regulations regarding the implementation of mediation at the village level as a preventive effort to resolve family-based agrarian conflicts.